The Relationship Between Social Engagement and Social Awareness Among Students in an Islamic Education Program - Khairunnikmah, Iffah; Nasir, Muhammad; Armella, Rega; Hasanah, Naomi Ainun (Borneo International Journal of Islamic Studies, 2025)
The globalization era with digital communication technology has led to a decline in social awareness within society. As agents of change, university students play an important role in building social concern through involvement in various activities. This research aims to examine the extent of influence that social activities have on the social awareness of Islamic Religious Education (PAI) students at UIN Sultan Aji Muhammad Idris Samarinda, who have demonstrated active participation in community service programs organized by HMPS PAI and the "Teman Panti" program by the EPIC community. This research employed a quantitative approach with correlational research design, while sampling was conducted using purposive sampling technique based on predetermined criteria. Data analysis included tests of normality, linearity, simple regression, correlation, coefficient of determination, and t-test to measure the influence and significance of relationships between variables. The research results demonstrate that social activities have a positive and significant effect on the social awareness of PAI students, with a significance value of 0.003 < 0.05 and t-count (3.156) > t-table (1.675). The correlation between the two variables falls in the medium category (Pearson Correlation 0.408), with social activities contributing 16.6% to students' social concern. These findings affirm the importance of social activities as an effective strategy in fostering social concern among university students.